The study of dream authenticity of the Prophet Muhammad saw among Muslims in Malaysia - Mohd Nizam, Sahad; Muhammad Fathullah Al Haq, Muhamad Asni; Siti Aishah Chu, Abdullah (African Journals Online, 2018)
In Islam, having dreams of the Prophet Muhammad SAW are not impossible and that they are counted as true dreams based on authentic hadiths. Nevertheless, it is a necessity to assess the right physique of the Prophet Muhammad SAW in the dream setting. Thus, the objectives of this study are to assess the informants’ knowledge of related hadiths on dream of the Prophet Muhammad SAW and to assess the authenticity of the informants’ dream of the Prophet Muhammad SAW. A qualitative content analysis approach was utilized in this study, whereby informants were interviewed and the data was then transcribed for analysis. A total of four informants were obtained through a snowball sampling technique. The study discovers that the four informants’ dream of the Prophet Muhammad SAW is true as the description of their dream is in parallel with related hadiths.